Quantitative Genetics for Plant Breeding - Suza, Walter; Lamkey, Kendall (Open textbook library., 2023)
This open textbook is intended to expose students to the application of quantitative genetic models to plant breeding populations. Specific topics include conducting and interpreting multi-environment trials, resource allocation using engineering principles, genetic modeling of quantitative traits, simulation modeling, variance, covariance and heritability, prediction, selection, and genetic gain.